A Comparative Study on Medical and Nursing Students Viewpoints about Telemedicine Procedures Development - Ahad Alizade; Akbar Mohammadi; Hadi Hosseini; Mohammad Khadmloo (Zanjan University of Medical Sciences and Health Services, 2014)
Background and Objectives: The aim of this study was to compare the viewpoints of medical and nursing students on development of telemedicine procedures at Mazandaran University of Medical Sciences. Materials and Methods: This was a cross-sectional study. Ninety medical students and 55 nursing students were selected using stratified random sampling in the first semester of 2011-2012. The studentschr('39') viewpoints on creation and development of telemedicine were measured using a questionnaire. The questionnaire included demographic section, and the studentschr('39') viewpoints on telemedicine and different telemedicine tools. The reliability of the questionnaire was assessed using the Cronbachchr('39')s alpha coefficient. Statistical tests were used to analyze the data including the t-test and ANOVA for quantitative variables and Mann-Whitney and Kruskal-Wallis and Chi-squared tests for qualitative variables. Results: There were significant relationships between information literacy and organizational factors with gender (P≤0.001). There were also significant relationships between the stakeholderschr('39') factors with gender and family location (P≤0.001). There were significant differences between the medical and nursing studentschr('39') viewpoints on the factor of stakeholders (p=0.029). Conclusion: Medical and nursing studentschr('39') viewpoints were similar except for the stakeholders factor. Community and family support for development of telemedicine tended to develop differences in the viewpoints of the students